Foliar Application of Silicon Enhances Resistance Against Phytophthora infestans Through the ET/JA- and NPR1- Dependent Signaling Pathways in Potato - Xue, Xiaojing; Geng, Tiantian; Liu, Haifeng; Yang, Wei; Zhong, Weiran; Zhang, Zhiliang; Zhu, Changxiang; Chu, Zhaohui (Frontiers in Plant Science, 2021)
Late blight (LB), caused by the oomycete pathogen Phytophthora infestans, is a devastating disease of potato that is necessary to control by regularly treatment with fungicides. Silicon (Si) has been used to enhance plant resistance against a broad range of bacterial and fungal pathogens; however, the enhanced LB resistance and the molecular mechanisms involving the plant hormone pathways remain unclear. In this study, Si treatment of potato plants was found to enhance LB resistance in both detached leaves and living plants accompanied by induction of reactive oxygen species (ROS) production and pathogenesis-related genes expression. Regarding the hormone pathways involved in Si-mediated LB resistance, we found a rapidly increased content of ethylene (ET) 15 min after spraying with Si. Increased jasmonic acid (JA) and JA-Ile and decreased salicylic acid (SA) were identified in plants at 1 d after spraying with Si and an additional 1 d after P. infestans EC1 infection. Furthermore, pretreatment with Me-JA enhanced resistance to EC1, while pretreatment with DIECA, an inhibitor of JA synthesis, enhanced the susceptibility and attenuated the Si-mediated resistance to LB. Consistent with these hormonal alterations, Si-mediated LB resistance was significantly attenuated in StETR1-, StEIN2-, StAOS-, StOPR3-, StNPR1-, and StHSP90-repressed plants but not in StCOI1- and StSID2-repressed plants using virus-induced gene silencing (VIGS). The Si-mediated accumulation of JA/JA-Ile was significantly attenuated in StETR1-, StEIN2-, StOPR3- and StHSP90-VIGS plants but not in StCOI1-, StSID2- and StNPR1-VIGS plants. Overall, we reveal that Si can be used as a putative alternative to fungicides to control LB, and conclude that Si-mediated LB resistance is dependent on the ET/JA-signaling pathways in a StHSP90- and StNPR1-dependent manner.